A compact portable photoacoustic sensor for sub-ppm level SO2 detection with a DUV-LED and a non-resonant photoacoustic cell - Jing, Yujing; Feng, Chaofan; Cui, Ruyue; Xue, Jiyu; Dong, Lei; Wu, Hongpeng (Frontiers in Physics, 2023)
A photoacoustic module based on a novel 273 nm deep-ultraviolet light-emitting diode (DUV-LED) was developed for sulfur dioxide (SO2) detection. The DUV-LED with an emission angle of 60° emitted a power of 10 mW. A high-sensitivity non-resonant photoacoustic cell with a gas chamber volume of only 0.39 mL was introduced to reduce the thermal noise generated by the contact of scattered DUV light with the photoacoustic cell. Assembly of the DUV-LED with the non-resonant photoacoustic cell resulted in a robust and portable photoacoustic module without any moving parts. The minimum detection limit of 725 ppb was achieved with 1s integration time at room temperature and atmospheric pressure. Furthermore, the photoacoustic module performance was evaluated in terms of DUV modulation frequency, linearity and the long-term stability.